Deteksi Edwardsiella tarda secara imunohistokimia pada ikan patin (Pangasius pangasius) - S. Andriyanto; Haririah Haririah; Y. Yulianti; S.H.I. Purnomo; S.T. Astuti; Nurlaila Nurlaila; T. Samudro; B. P. Priosoeryanto (Hemera Zoa, 2009)
Detection of Edwardsiella tarda antigen on the 20 heads of experimentally infected-catfish tissue (Pangasius pangasius) by immunohistochemistry was done. Clinical sign of the infected fish were weak response, swelling, haemorrhages in the anal, abdomen and tail fin regions, ulcer in the above of linea lateralis. Gross findings of the internal organs were swelling, pale and bad smell. Histopathologically, there were necrotic area with  infiltration of inflamatory cells, melanomacrophages in the muscle, liver, kidney and spleen and some eosinophilic materials in the kidney was also found.  Immunohistochemical detection using specific antibody to E. tarda showed positive reaction in the internal organs.  Immunohistochemistry assay is one of the suitable methods for detection and diagnose of E. tarda infrction in fish.Keywords: Catfish, Edwardsiella tarda, immunohistochemistry